Machine learning for data classification in construction project planning - Lau, Zheng Liang (2023)
Machine Learning is a tool of Artificial Intelligence to use the algorithms and statistical models to enable a machine to learn the concept and make predictions or decision as an outcome. The Machine learning is a tool created from statistical principles and expanded into the world. The concept of the Machine Learning is the ability of the machine able to learn the situation with algorithms rules and make a predictions or decision. Hence, it is useful to develop in different area in the real world. The Machine Learning can develop into many areas which are Gaming, Data Mining and Analysis, Recommendation System, Financial Management and so on. In the country of Malaysia, most of the project companies are process the traditional method to analysis the project budget. In beside of the situation, most of the companies fear the Artificial Intelligence is taking over on the business. As known, the project budget is important to a project company to make sure the project they taken is reasonable and suitable from the client given. The project company choose the project they take and discuss with the client on the project’s budget. Most of the reason the project taken was over the budget is lack of understand of the project and spend a lot of cost on time management and project scope. In the situation, Machine learning model helps the project company to analyze the project and decision the advice in project planning management. It helps to most project companies increase business strategy with Machine Learning model. Resulting the project company easier make decision in the project planning without distressed. Based on business information management, Machine Learning is the most recommended technologies tool to supports many project companies and SME in their business growing. This project is to proof the Machine Learning can develop for the local business project company.